Patient satisfaction with medical consultations among adults attending Mulago hospital assessment centre - Angella Kabatooroa; Fred Ndoboli; Jane Namatovu (South African Family Practice)
Background: Patient satisfaction is known to positively influence patients’ compliance with medical advice. In Africa, and specifically Uganda, this interaction has rarely been put to scientific inquiry. This study aimed to determine the level of patient satisfaction and identify factors influencing satisfaction with medical consultations among adults attending Mulago Assessment Centre.